Estimating a high-frequency New-Keynesian Phillips curve - Steffen Ahrens; Stephen Sacht (Kiel Institute for the World Economy (IfW), 2011)
This paper estimates a high-frequency New Keynesian Phillips curve via the Generalized Method of Moments. Allowing for higher-thanusual frequencies strongly mitigates the well-known problems of smallsample biases and structural breaks. Applying a daily frequency allows us to obtain eventspecific estimates for the Calvo parameter of nominal rigidity - for instance for the recent financial and economic crisis -, which can be easily transformed into their weekly, monthly and quarterly equivalences to be employed for the analysis of eventspecific monetary and fiscal policy. With Argentine data from the end of 2007 to the beginning of 2011, we find the daily Calvo parameter to vary in a very close range around 0.97, which implies averagely fixed prices of approximately 40 days or equivalently one and a half month or a little less than half a quarter. This has strong implication for the modeling of monetary policy analysis since it implies that at a quarterly frequency a flexible price model has to be employed. In the same vein, to analyze monetary policy in a sticky price framework, a monthly model seems more appropriate.
Keywords: C26; C63; E31; 330; Calvo Staggering; High-Frequency NKM; GMM; New-Keynesian Phillips Curve; Momentenmethode; Schätzung; Argentinien